MODELING USING DISCRIMINATION ANALYSIS, PRIORITY OF PRACTICALLY HEALTHY MEN TO NORTHERN OR OTHER ADMINISTRATIVE-TERRITORIAL REGIONS OF UKRAINE ON THE BASIS OF DERMATOGLYPHIC INDICATORS FEATURES - Gunas, V.I. (World of Medicine and Biology, 2018)
In the article, the analysis of discriminatory models of the affiliation of practically healthy men to the northern or other administrative-territorial regions of Ukraine on the basis of peculiarities of finger and palmar dermatologic indices was constructed and analyzed. The highest level of discrimination was found among the men of the northern and southern and northern and eastern regions of Ukraine. Most often discriminant variables between men of the northern and other regions of Ukraine are the type of pattern on the fingers of the right hand and the asymmetry of the comb account of the lines a-b and c-d. The largest contribution to discrimination between northern and other administrative-territorial regions of Ukraine has the asymmetry of the comb account of the lines a-b and c-d.
Keywords: discriminatory analysis; dermatoglyphic; practically healthy men